The interplay between hemostasis and immune response in biomaterial development for osteogenesis. (April 2022) - Xiao, Lan; Ma, Yaping; Crawford, Ross; Mendhi, Jayanti; Zhang, Yi; Lu, Haiping; Zhao, Qingyu; Cao, Jin; Wu, Chengtie; Wang, Xin; Xiao, Yin
Graphical abstract: Abstract: Treatment of large bone defects, particularly bone non-union, remains a clinical challenge. The gold-standard bone substitute continues to be an autologous bone graft, which is difficult to be replaced with synthetic biomaterials. Considering these aspects, strategies should be formulated to develop advanced materials for functional bone regeneration. Recent studies have revealed that hematoma (the first tissue structure formed at the bone injury site) plays an essential role in bone healing. Hematoma consists of a fibrin clot, infiltrated immune cells, and tissue progenitor cells. It bridges the bone defect and provides a microenvironment for the interplay between hemostasis and the immune systems. Moreover, an ideal fibrin structure with appropriate fiber thickness and density could facilitate bone regeneration, and biomaterial implantation could affect fibrin structure. Meanwhile, immunoregulation plays an essential role in bone healing. In particular, materials inducing a shift from inflammatory to anti-inflammatory phenotypes in immune cells show enhanced osteoinductivity. More importantly, the interaction between hemostasis and the immune system should play a vital part in bone regeneration by determining both fibrin structure and bone healing microenvironment. Coagulants-triggered inflammation could, in turn, facilitate coagulation cascades, which form positive feedback to amplify both processes. Meanwhile, anti-coagulants neutralize coagulation and inhibit inflammation and thereby control the coagulation and inflammation to prevent thrombosis. The balance between coagulation–inflammation and anti-coagulation–anti-inflammation plays a determinant role in the fibrin structure and fibrinolysis process. The inflammation could be "quenched" gradually during this process, whereby a highly effective microenvironment for bone regeneration can be generated. Presently, there are limited biomaterial studies targeting the bone-healing hematoma, particularly the hemostasis–immune interplay. Considering this, this review summarizes the current materials for hemostasis and immunomodulation, and the critical role of the hemostasis–immune interaction in bone regeneration. It also proposes potential strategies to develop materials with the capacity to generate a highly effective bone healing hematoma, by modulating the hemostasis–immune interplay to maintain the balance between coagulation–inflammation and anti-coagulation–anti-inflammation.